2021
DOI: 10.1111/1462-2920.15713
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of stochastic processes to the microbial community assembly on field‐collected microplastics

Abstract: Summary A growing body of evidence suggests that microplastics may be colonized with a unique microbiome, termed ‘plastisphere’, in aquatic environments. However, the deep mechanisms (deterministic and/or stochastic processes) underlying the community assembly on microplastics are still poorly understood. Here, we took the estuary of Hangzhou Bay (Zhejiang, China) as an example and examined the assembly mechanisms of bacterial communities in water and microplastic samples. Results from high‐throughput sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…To date, studies have explored the dynamics of microbial communities inherited from conventional non-degradable plastics in aqueous environments by means of null modeling-based or neutral theory-based approaches. Most studies demonstrated the dominant role of stochastic processes in plastisphere microbiota ( Sun et al, 2021 ; Zhang et al, 2021 ; Zhu et al, 2021 ), and a few suggested a higher influence of deterministic ecological processes ( Hou et al, 2021 ; Li et al, 2021a ). None of previous studies presented the microbial assembly of BDMs in soils.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, studies have explored the dynamics of microbial communities inherited from conventional non-degradable plastics in aqueous environments by means of null modeling-based or neutral theory-based approaches. Most studies demonstrated the dominant role of stochastic processes in plastisphere microbiota ( Sun et al, 2021 ; Zhang et al, 2021 ; Zhu et al, 2021 ), and a few suggested a higher influence of deterministic ecological processes ( Hou et al, 2021 ; Li et al, 2021a ). None of previous studies presented the microbial assembly of BDMs in soils.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller selective role may imply that the plastisphere microbial community was more resistant to changes in plastic components and environmental factors. Many previous studies have found that properties of plastics and environmental factors largely affected the composition and assembly mechanism of microbial communities ( Li et al, 2021a ; Sun et al, 2021 ). One of the possible explanations for the lower selection observed in our study is that the samples were only collected in our potted soils.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations